1977
DOI: 10.1104/pp.59.3.384
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis in Relation to Leaf Characteristics of Cotton from Controlled and Field Environments

Abstract: In situ and light-saturated net photosynthetic rates per unit leaf area were greater in cotton (Gossypium hirsultum L.) plants grown in pots in the field than in similar plants from a phytotron growth chamber. Lightsaturated stomatal resistances did not differ in leaves of similar age and exposure on field and chamber plants; lower photosynthetic rates in chamber leaves were associated with greater mesophyli resistance. Differences in net photosynthetic rates were related to differences in leaf thickness. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 19 publications
6
37
0
Order By: Relevance
“…Oscillations in the amount of Chl could explain the rhythm in photosynthetic rate at saturating light intensities (1,28). However, when Euglena is grown in constant dim light no obvious rhythm in Chl content (total mg Chl/cell) could be detected (data not shown).…”
Section: Pm) Photosynthesis Rhythm In Euglenamentioning
confidence: 96%
“…Oscillations in the amount of Chl could explain the rhythm in photosynthetic rate at saturating light intensities (1,28). However, when Euglena is grown in constant dim light no obvious rhythm in Chl content (total mg Chl/cell) could be detected (data not shown).…”
Section: Pm) Photosynthesis Rhythm In Euglenamentioning
confidence: 96%
“…These increases in the amount of photosynthetic tissue included increases in mesophyll thickness (or volume/unit area), Chl content/unit area, PSU density/unit area, and specific leaf weight. Other workers have also shown that quantitative changes in the photosynthetic apparatus are important in accounting for photosynthetic adaptability to irradiance (7,13,14,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Stomatal and boundary layer resistances were subtracted from the total resistance to yield residual or mesophyll resistance. This calculation of mesophyll resistance includes differences in carboxylase activity as well as all other nonboundary layer and nonstomatal effects (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CO2 concentration was 350 or 1000 Ml L-' CO2. Plant density was 97 m 2 before transplanting (15 d Thirty five, 42, and 58 d after seeding gas exchange was measured using a small, hand-held cuvette enclosing both upper and lower leaf surfaces Patterson et al [21 ] for cuvette description) and a Beckman 865 IR gas analyzer. All measurements were made inside the growth chambers, selecting the uppermost fully expanded leaf on each of eight plants.…”
Section: Methodsmentioning
confidence: 99%